The Prognostic Role of Pitt Bacteremia Score in Patients With Nonbacteremic Klebsiella pneumoniae Infections - Jia-Mei Chang; Kuo-Hsuan Lin; Chung-Hsu Lai; I-Ting Tsai; Yin-Chou Hsu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: PBS correlated with adverse outcomes and good mortality prediction ability in patients with nonbacteremic K. pneumoniae infections.